Abandonada (Viva Films, 2001)
After working in Canada for a long time, Gemma returns to the country and comes home to an abandoned house. Later she finds her husband Edwin in a new home with a new wife Cindy with her 4-year old son Michael. Gemma applies as househelp Cindy's house without Edwin's knowledge to get her son back. After, when Gemma saved their daughter, Edwin learns that Gemma is in the country, much worse, that she has been working for his new family in his new household. The unfolding of the truth eventually leads to a change of heart for Cindy that she aids Gemma in her pursuit to regain what is truly hers.